Female Robots and AI in Science Fiction Cinema - Jones, Rebecca L. author. (orcid)0000-0002-6218-5333 Link aut Link
VII, 307 p. 1 illus.
Keywords: This book is the first comprehensive overview of the history of female-presenting AI and robots in US and UK live-action, science fiction films from 1949 to 2023. It offers an original taxonomy that aids in the examination of 80 films and over 135 characters’ representations, starting with The Perfect Woman (1949) and ending with Robots (2023). Using its representational taxonomy, this book analyses the evolution of these depictions, showing the continuations, revisions, and shifts in the depiction of female-presenting AI and robots from objectified, eroticised, subordinated things to being autonomous moral agents who assert their right to equality and refuse their abusive, typically sexual, use. This book shows how these fictional, gendered constructions are products of a heterosexual, cisgender, male fantasy of an idealised, subordinated form of femininity. These artificial characters, along with their real-world counterparts, highlight a desire for a subordinated femininity, but also show how that subordination is a social construction often reinforced and countered in onscreen depictions. By examining the trends within its asserted Galatea, Girlfriend, Mother, and Deadly Seductress types, this book presents an exploration of what our female-presenting artificial creations could be, while addressing their contemporary, and our current, AI technologies, and how science fiction is influencing real life, while our reality seeks to mirror science fiction. Dr Rebecca L Jones, PhD, is an Associate Lecturer at University of Maryland, College Park, USA. She writes about representation across media types in journals such as Fantastika and MAI: A Journal of Feminism and Visual Culture, and in edited collections on gender and contemporary horror, autonomous weapons systems, and cybernetics.